2011
DOI: 10.1149/1.3635686
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conductivity and Partial Molar Volume of Different Polymer Electrolyte Membranes

Abstract: Density and water uptake were measured for a series of 3M ionomer membranes with different acid groups and equivalent weight (ew). We have developed a systematic method for measuring the density of hydrated membranes and assessed its statistics. In gas pycnometry, a pressure change is measured upon inserting a sample into a calibrated volume of gas. The density of several perfluorosulfonic acid (PFSA) membranes was measured as a function of water content. We also calculate the partial molar volume of water in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
5
7
0
Order By: Relevance
“…Further evidence in support of the 3-stage absorption process described above has been provided recently by Bai et al, 21,22 who also observed a dramatic, almost linear increase in the partial molar volume of water with increasing hydration level in several types of ionomeric membranes, including PFSAs. These authors showed that the membranes examined displayed a linear increase in the partial molar volume of water contained as a function of hydration level, specifically over ranges of water numbers approximately covering λ ∈ [2,6].…”
Section: Modeling Conductivity Of a Hydrated Membranesupporting
confidence: 63%
See 2 more Smart Citations
“…Further evidence in support of the 3-stage absorption process described above has been provided recently by Bai et al, 21,22 who also observed a dramatic, almost linear increase in the partial molar volume of water with increasing hydration level in several types of ionomeric membranes, including PFSAs. These authors showed that the membranes examined displayed a linear increase in the partial molar volume of water contained as a function of hydration level, specifically over ranges of water numbers approximately covering λ ∈ [2,6].…”
Section: Modeling Conductivity Of a Hydrated Membranesupporting
confidence: 63%
“…10 This is consistent with findings from previous experiments of Zawodzinski et al, who found a distinct transition in water vapor activity (i.e., solvation level) at a critical water content of approximately λ ≈ 5 in the N, C, D, and 3M membranes. [21][22][23][24][25] Again, these experiments appear to align with the hypothesis that conductivity at low water content is primarily limited to vehicular diffusion, or diffusion of hydronium ions between clusters once the percolation threshold has been achieved and a solvation layer interposed between the contact ion pairs of hydroniums and sulfonate groups.…”
Section: Modeling Conductivity Of a Hydrated Membranesupporting
confidence: 60%
See 1 more Smart Citation
“…At a given equivalent weight, the 3M membrane has a higher content of PTFE backbone than Nafion membrane, which improves the mechanical properties and leads to a higher proton conductivity at higher temperatures and dryer operation conditions . Recently, the 3M membrane has received a great deal of attention and achieved excellent performance for RFBs or fuel cell applications. The impact of pretreatment has not yet been researched, though.…”
Section: Introductionmentioning
confidence: 99%
“…Simulated density of PFIA at T=300 K and T=353 K and experimental[78] density at T=300 K. The errors values of the simulated density are very small (order of 10 -5 ) and hence not shown here.Simulated density values have been used as a criteria for judging the accuracy of the force field for classical MD simulations of PEMs[26][28][38][39][68][71]. Therefore, the choice of force field for our simulations are well suited for analysing PFIA since the simulated density values are close to the experimental values.…”
mentioning
confidence: 99%